Applicability of the Graetz's solution for Newtonian fluids to the calculations of the heat transfer in coal-water fuel at the pre-heating stage. (1st March 2021) - Pinchuk, Valeriya; Moumane, Mohammed; Sharabura, Tatiana; Shishko, Yulia; Kuzmin, Andrey
Highlights: pre-heating allows activating the coal-water fuel before using. heat transfer related solution for Newtonian fluids is not applicable for coal-water fuel. empirical equation of simple form is provided as the result of the experimental research. Abstract: The usage of coal-water fuel requires some preparations and activation of the fuel before combustion. One of the preparation stages is coal-water fuel's thermal activation which improves the burning processes of such a fuel. This manuscript considers specifics of the coal-water fuel pre-heating in the feeding pipe. The results show that the widely used Graetz's solution for Newtonian fluids cannot be used for calculation of the heat-transfer parameters in the case of coal-water fuel. An empirical equation was obtained for use in practical applications.